2015
DOI: 10.14746/ssllt.2015.5.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Emotion as the amplifier and the primary motive: Some theories of emotion with relevance to language learning

Abstract: Emotion is crucial to living and learning. The powerful intertwining of emotion and cognition ignites learning within a complex dynamic system, which, as several sections of this paper show, also includes societal and cultural influences. As "the primary human motive" (MacIntyre, 2002a, p. 61), emotion operates as an amplifier, which provides energetic intensity to all human behavior, including language learning. This chapter explains major theories of emotion drawn from positive psychology, social psychology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…Consequently, emotions indeed seem to assist adaptation to our physical and social environment and ensure our survival. Therefore, Oxford (2015) seems to be right when arguing that "all learning is a powerful combination of cognition and emotion" (p. 371).…”
Section: What Are Emotions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, emotions indeed seem to assist adaptation to our physical and social environment and ensure our survival. Therefore, Oxford (2015) seems to be right when arguing that "all learning is a powerful combination of cognition and emotion" (p. 371).…”
Section: What Are Emotions?mentioning
confidence: 99%
“…The recent shift in focus, to other emotions and positive emotions in particular, can be attributed to the emergence of positive psychology (Seligman & Csíkszentmihályi, 2000) and its focus on positive emotions, for example. Fredrickson's (2003Fredrickson's ( , 2008 theory hypothesizing the crucial role of positive emotions found its way into research on second and foreign language acquisition (Dewaele & MacIntyre, 2014;MacIntyre & Gregersen, 2012;MacIntyre & Mercer, 2014;MacIntyre & Vincze, 2017, Oxford, 2015. More specifically, Fredrickson's (2003Fredrickson's ( , 2008 broaden-and-build theory postulates that negative emotions tend to lead to characteristic thoughts and actions; thus, they result in focusing and narrowing.…”
Section: What Are Emotions?mentioning
confidence: 99%
“…Furthermore, CLIL is also believed to have a positive impact on socio-affective variables such as language attitudes, motivation and anxiety (Lasagabaster, 2009). However, while the last decade has witnessed a growing interest in the role of both positive and negative emotions in language learning (Dewaele, 2005a(Dewaele, , 2015MacIntyre & Gregersen, 2012Oxford, 2015;Ross & Stracke, 2016), few large-scale and/or longitudinal studies have investigated those aspects in CLIL so far. Therefore, the present study, as part of a larger multidisciplinary and longitudinal research project assessing CLIL in French-speaking Belgium, aims to address this gap in the literature by investigating anxiety and enjoyment in CLIL and non-CLIL.…”
Section: Introductionmentioning
confidence: 99%
“…The domain of language learning and emotions is marked by several key concepts such as motivation, willingness to communicate, self-efficacy and (foreign) language anxiety (Simons & Smits, 2018). In the last decade we have witnessed a growing interest in the influence of positive emotions on language learning (Dewaele, 2005(Dewaele, , 2015Gregersen et al, 2014;2016;Oxford, 2015;Ross & Starcke, 2016;Seligman & Csikszentmihalyi, 2000), At the same time, we observe a renewed and global interest in the emotion and psychological construct of Foreign Language Research into the link between CLIL and FLA is recent and scarce. Macintyre, Baker, Clement and Donovan (2003) applied a survey with a qualitative section to study the effects of language, sex and grade on FLA, willingness to communicate (WTC), and perceived communicative competence in CLIL and traditional classes in a Canadian junior high French late immersion programme.They found that students' L2 WTC, perceived competence, and frequency of communication in French increased from grades 7 to 8 and was maintained between grades 8 and 9, despite a drop in motivation between grades 7 and 8 and a steady level of FLA across the three grades.…”
Section: Theoretical Frameworkmentioning
confidence: 99%